SOCIO-ECONOMIC CONDITION OF SHUDRAS DURING THE POST-MAURYAN PERIOD(200 BCE – 300 CE) - Kumari, Dr. Preeti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The post-Mauryan period (200 BCE – 300 CE) was a transformative phase in Indian history, marked by political fragmentation and socio-economic changes. The decline of the Mauryan Empire led to the rise of regional dynasties such as the Shungas, Satavahanas, Kushans, and early Guptas, each of which played a significant role in shaping social structures and economic conditions. Among the most affected groups were the Shudras, who occupied the lowest position in the four-fold varna system.1During this period, Brahmanical ideology, as reflected in texts like the Manusmriti, reinforced the idea that Shudras were meant to serve the upper varnas and restricted their access to education and religious participation.2 However, alternative religious movements such as Buddhism and Jainism provided Shudras with opportunities for social and religious engagement. Some Shudras were able to improve their economic status by engaging in trade, craftsmanship, and labor-intensive industries, especially in growing urban centers like Mathura, Ujjain, and Pataliputra.3Economically, the post-Mauryan period saw significant agricultural expansion, urbanization, and trade growth. Shudras played a crucial role as farmers, laborers, artisans, and craftsmen.4 In some cases, they gained economic prosperity by participating in commercial activities, but the overall rigid caste hierarchy limited their upward mobility.5Heavy taxation and forced labor (vishti) remained significant burdens on Shudras, reinforcing their economic hardships.6This study examines the socio-economic condition of Shudras during the post-Mauryan period based on historical texts, inscriptions, and scholarly analyses. The following references provide detailed insights into their status during this period of transition.7